2015
DOI: 10.1002/lary.25459
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of site of obstruction identification and non‐CPAP treatment options for children with persistent pediatric obstructive sleep apnea

Abstract: Drug-induced sleep endoscopy and cine MRI are the most commonly reported tools to identify sites of obstruction for children with persistent OSA; however, these techniques have not yet been clearly linked to outcomes. Evidence for treatment is extremely limited and focuses primarily on lingual tonsillectomy and supraglottoplasty. Also, reports regarding appropriate patient selection and outcomes in obese or otherwise healthy children are scant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 43 publications
5
84
0
3
Order By: Relevance
“…Manickam et al reviewed 4 studies using supraglottoplasty as a salvage treatment for persistent OSA after adenotonsillectomy [36]. Camacho et al revealed that supraglottoplasty improved the AHI and MinSaO 2 in children with congenital and sleep-exclusive laryngomalacia.…”
Section: Comparison With Previous Reviewsmentioning
confidence: 98%
See 2 more Smart Citations
“…Manickam et al reviewed 4 studies using supraglottoplasty as a salvage treatment for persistent OSA after adenotonsillectomy [36]. Camacho et al revealed that supraglottoplasty improved the AHI and MinSaO 2 in children with congenital and sleep-exclusive laryngomalacia.…”
Section: Comparison With Previous Reviewsmentioning
confidence: 98%
“…Two previous reviews have offered valuable insights regarding supraglottoplasty in treating pediatric OSA [36,38]. Manickam et al reviewed 4 studies using supraglottoplasty as a salvage treatment for persistent OSA after adenotonsillectomy [36].…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, currently there is limited evidence to support the routine use of these procedures [47]. The benefit of these more aggressive surgical options for OSA specifically in the DS group is also unclear; Merrell and Shott [43] evaluated the use of lateral pharyngoplasty with adenotonsillectomy in the initial treatment of OSA in children with DS and found no additional benefit when compared to adenotonsillectomy alone.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%
“…However, these techniques have not yet been clearly linked to outcomes [47].Therefore, at present conservative treatment with continuous positive airway pressure (CPAP) or less commonly, bi-level (BPAP) therapy, is often preferred for management of residual OSA, preventing the need for further invasive surgical procedures including tracheostomy. Such therapy is however challenging in paediatrics and even more so in patients with DS, where behavioural and intellectual impairment may hinder the establishment and adherence to therapy.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%